2021
DOI: 10.1002/ijgo.13709
|View full text |Cite
|
Sign up to set email alerts
|

The association between smoking during pregnancy and hypertensive disorders of pregnancy: A systematic review and meta‐analysis

Abstract: Background Smoking is a major public health problem. However, its association with hypertensive disorders of pregnancy (HDP) is inconclusive. Objective To find the association between smoking during pregnancy and HDP. Search strategy We searched PubMed, Ovid and Cochrane Library up to March, 2021, using terms including “smoking” and “HDP”. Selection criteria Observational studies that assessed the relationship between smoking during pregnancy and HDP were included. Data collection and analysis Odds ratios (OR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
(139 reference statements)
2
21
4
1
Order By: Relevance
“…The frequency of stillbirth was too small to estimate an adjusted OR. Other studies found a reduced risk of HDP 37 38 with maternal smoking, although we did not replicate this association.…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of stillbirth was too small to estimate an adjusted OR. Other studies found a reduced risk of HDP 37 38 with maternal smoking, although we did not replicate this association.…”
Section: Discussioncontrasting
confidence: 99%
“…Other risk factors for HDP include a previous history of HDP 93 , 98 , 99 , a family history of HDP 93 and pre-existing diseases, such as chronic hypertension, pregestational diabetes mellitus, thrombophilia, systemic lupus erythematosus, antiphospholipid antibody syndrome, kidney disease and obstructive sleep apnoea 16 , 93 , 94 , 97 . Smoking has been revealed to be a potential protective factor for HDP 100 , but the evidence of the association between smoking during pregnancy and HDP remains controversial 101 , 102 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…A systematic review based on 13 studies revealed that in Asia smoking is a risk factor for hypertensive disorders of pregnancy. 14 Prevalence of PIH was more in the women with higher prepregnancy BMI (≥25) with a prevalence of about 10% than the women with lower BMI with a prevalence of 3.3% and this relationship was statistically significant (p=0.007). Similar findings have been noted in most of the studies.…”
Section: Discussionmentioning
confidence: 80%